this is q.2 of ahlfors p. 241: Show that $$\int_{-1}^{1}\frac{dt}{\sqrt {(1-t^2)(1-k^2t^2)}}=\int_{1}^{\frac{1}{k}}\frac{dt}{\sqrt {(t^2-1)(1-k^2t^2)}}$$ if and only if $k=(\sqrt{2}-1)^2$ . Thank you.

  • 1
    $\begingroup$ Lars (I assumed you meant Lars) Ahlfors wrote several books. Perhaps you should specify which one. $\endgroup$ – Willie Wong Apr 26 '13 at 14:31

This is basically an exercise in elliptic function theory. The integral on the left is clearly equal to $\displaystyle I_{1} = 2\int_{0}^{1}\frac{dt}{\sqrt{(1 - t^{2})(1 - k^{2}t^{2})}} = 2\int_{0}^{\pi/2}\frac{d\theta}{\sqrt{1 - k^{2}\sin^{2}\theta}} = 2K(k)$

The integral on right is bit tricky. But we have to see that by definition of elliptic function $\text{sn}(u, k)$ we have $\displaystyle u = \int_{0}^{\text{sn}(u, k)}\frac{dt}{\sqrt{(1 - t^{2})(1 - k^{2}t^{2})}}$ and we need to use the knowledge that $\text{sn}(K + iK', k) = 1/k$ so that $\displaystyle K + iK' = \int_{0}^{1/k}\frac{dt}{\sqrt{(1 - t^{2})(1 - k^{2}t^{2})}}$

Then we can see that

$\displaystyle K + iK' = \int_{0}^{1}\frac{dt}{\sqrt{(1 - t^{2})(1 - k^{2}t^{2})}} + \int_{1}^{1/k}\frac{dt}{\sqrt{(1 - t^{2})(1 - k^{2}t^{2})}}$ $\displaystyle \Rightarrow iK' = \int_{1}^{1/k}\frac{dt}{\sqrt{(1 - t^{2})(1 - k^{2}t^{2})}}$

$\displaystyle \Rightarrow K' = \int_{1}^{1/k}\frac{dt}{\sqrt{(t^{2} - 1)(1 - k^{2}t^{2})}}$

So your original equation between integrals becomes $K'(k) = 2K(k)$ or $K'(k)/K(k) = \sqrt{4}$. Now clearly this means that $k$ is a singular modulus $k_{n}$ with $n = 4$. The value of $k = k_{4}$ is a standard one given by $k = (\sqrt{2} - 1)^{2}$.

A complete understanding would require one to read material on elliptic functions, class invariants and singular moduli. Some of this material is presented in my blog : http://paramanands.blogspot.com/2011/01/elliptic-functions-introduction.html http://paramanands.blogspot.com/2012/03/ramanujans-class-invariants.html

To obtain the value of $k$ we can use the Landen's transformation (http://paramanands.blogspot.com/2009/08/pi-and-the-agm-evaluating-elliptic-integrals.html) directly to get $$K(k) = \frac{1}{1 + k}K\left(\frac{2\sqrt{k}}{1 + k}\right)$$ and if we put $l = 2\sqrt{k}/(1 + k)$ we can see that $k = (1 - l')/(1 + l')$ so that we express the same relation as $$K(l) = \frac{2}{1 + l'}K(k)$$ and we can also see that $k' = 2\sqrt{l'}/(1 + l')$ and hence if we replace $k$ by $l'$ in first relation above we get $$K(l') = \frac{1}{1 + l'}K\left(\frac{2\sqrt{l'}}{1 + l'}\right) = \frac{1}{1 + l'}K(k')$$

On division we now obtain $$\frac{K(k')}{K(k)} = 2\frac{K(l')}{K(l)}$$ where $k = (1 - l')/(1 + l')$. If we put $l = 1/\sqrt{2}$ so that $l' = \sqrt{1 - l^{2}} = 1/\sqrt{2} = l$ then we see that we have $$\frac{K(k')}{K(k)} = 2$$ where $$k = \dfrac{1 - \dfrac{1}{\sqrt{2}}}{1 + \dfrac{1}{\sqrt{2}}} = (\sqrt{2} - 1)^{2}$$

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.